PENGARUH PUPUK AGROBOST DAN HUMAGOLD TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG KETAN (Zea mays ceratina) - Suryawati Hamzah; Sri Utami; M.Abd. Cholik (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThe study was conducted to obtain the proper concentration of humagoldand  agrobost fertilizer in promoting growth and production of corn. Using a factorial randomized block design each treatment Ao = without agrobost,  A1 = 15 cc / l of water,  and A2  = 30 cc / l of water,  is the first factor. The second factor treatment,  Ho = without humagold, H1  = 15 cc / l of water, H2  = 30 cc / l of water. The results showed agrobost fertilizers 30 cc / l of water,  ( A2 )  obtained the highest results of observations of plant height, leaf number, stem diameter, weight and length of cob, while humagold  fertilizer and interaction with agrobost and humagold have a real influence / very real at all parameter observations.